Sperm-borne small non-coding RNAs: potential functions and mechanisms as epigenetic carriers - Muhammad Naveed; Zhaokang Shen; Jianqiang Bao (Cell & Bioscience)
Abstract Over the past two decades, the study of sperm-borne small non-coding RNAs (sncRNAs) has garnered substantial growth. Once considered mere byproducts during germ cell maturation, these sncRNAs have now been recognized as crucial carriers of epigenetic information, playing a significant role in transmitting acquired traits from paternal to offspring, particularly under environmental influences. A growing body of evidence highlights the pivotal role of these sncRNAs in facilitating epigenetic inheritance across generations. However, the exact mechanisms through which these paternally supplied epigenetic carriers operate remain unclear and are under hot debate. This concise review presents the most extensive evidence to date on environmentally-responsive sperm-borne sncRNAs, encompassing brief summary of their origin, dynamics, compartmentalization, characteristics, as well as in-depth elaboration of their functional roles in epigenetic and transgenerational inheritance. Additionally, the review delves into the potential mechanisms by which sperm-delivered sncRNAs may acquire and transmit paternally acquired traits to offspring, modulating zygotic gene expression and influencing early embryonic development.